Mutant strains of Streptomyces cinnamonensis protoplasts. Cultural and physiological conditions - Matĕjů, J; Marsálková, J; Nohýnek, M; Steinerová, N (Folia microbiologica, 1991)
Mycelium of Streptomyces cinnamonensis mutant strains cultivated in a synthetic medium with glycine produced protoplasts after lysis of cell walls with lysozyme. The protoplast yield was up to 95%. The protoplasts could revert and mycelial forms were thus regenerated. In a sucrose-containing medium the protoplasts stored at 4 degrees C were stable for 2 d.
Keywords: Glycine; Culture Media; Muramidase; mutace; Mutation; Protoplasts; mykologie; protoplasty; glycin; muramidasa; kultivační média; Mycology; Streptomyces